Linguagens, experiências e convenções de gênero e sexualidade no BDSM - Silva, Marcelle Jacinto da (2012)
The research that resulted in the construction of this work proposes dialogues between ethnography in virtual environment, sexuality, identity and self writing, taking as empirical cut blogs that express female experiences and reflections on erotic sadomasochism. We seek to highlight, through the observation of these blogs, which are meant to experiences of subjects entered into a subculture surrounded by stereotypes and stigmas, created and conducted for the purpose of avoiding or decriminalize BDSM, the fact that many incur in concern to differentiate erotic sadomasochism sadomasochism "unhealthy" and / or "criminal", and end up serving as a reference for beginners, curious or even exchange of experience between practitioners. The reflections throughout the text revolve around the issue of borders, the production of identities from which subcultures considered dissidents, transgressive. The boundaries do not represent limits, dead ends, but new ways they appear new meanings. The BDSM is an example border, as a subculture (or culture, depending on the point of gaze of the beholder) that challenges concepts such as violence, limits, performance, gender.